2021
DOI: 10.3390/app112411740
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelastic and Aerodynamic Tests of Wind Turbine with Various Polygonal Towers

Abstract: Traditionally, circular cross-section towers have been used as supporting systems of wind turbines, but weaknesses have become apparent with recent upsizing of wind turbines. Thus, polygonal cross-section towers have been proposed and used in Europe. In this study, the effects of polygonal cross-sections on the aeroelastic and aerodynamic characteristics of wind turbines were examined through a series of wind tunnel tests. Aeroelastic tests showed that a square cross-section tower showed instability vibrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Wind tunnel testing is a reliable method to obtain the aerodynamic characteristics of slender tower-like structures. Kim et al [1], using wind tunnel tests, found that polygonal towers have better aerodynamic stability and vibrational response than traditional circular towers. Mannini et al [2] focused their wind tunnel experimental studies on the aerodynamic loads during the pre-assembly stage of offshore wind turbine towers, discovering that the height of the tower significantly impacts aerodynamic loads.…”
Section: Introductionmentioning
confidence: 99%
“…Wind tunnel testing is a reliable method to obtain the aerodynamic characteristics of slender tower-like structures. Kim et al [1], using wind tunnel tests, found that polygonal towers have better aerodynamic stability and vibrational response than traditional circular towers. Mannini et al [2] focused their wind tunnel experimental studies on the aerodynamic loads during the pre-assembly stage of offshore wind turbine towers, discovering that the height of the tower significantly impacts aerodynamic loads.…”
Section: Introductionmentioning
confidence: 99%